The Relationship between Family Functions in Health Care with the Nutritional Status of the Elderly - Sugiarto, Kresna Bagus; Efendi, Zainudin (Journal of Language and Health, 2024)
The relationship between family function in health care and the nutritional status of the elderly is crucial in improving elderly nutrition. Effective family function, particularly in families with elderly members, plays a vital role in preventing malnutrition. This study aims to analyze the relationship between family function in health care and the nutritional status of the elderly in the working area of Kedungrejo Muncar Health Center, Banyuwangi. The study employed an analytical survey with a cross-sectional design, involving 50 respondents comprising elderly individuals and their families. Respondents were selected using a saturated sampling technique. Data collection was conducted through structured questionnaires and anthropometric measurements. The questionnaire assessed family functions in health care, while nutritional status was determined using body mass index (BMI) classifications based on weight and height measurements. Data were analyzed using the Spearman Rank test to examine the correlation between family function and nutritional status.The findings revealed that 42% of respondents exhibited poor family function in health care, and 66% of the elderly had a thin nutritional status. Statistical analysis demonstrated a significant positive correlation between family function in health care and the nutritional status of the elderly (r = 0.021; Sig < 0.05). These results indicate that better family function is associated with improved nutritional outcomes, while poor family function increases the risk of malnutrition.In conclusion, enhancing family function in health care is critical to ensuring adequate nutrition and preventing malnutrition among the elderly. Health workers play an essential role in raising awareness by providing counseling and education to families on their responsibilities in elderly care. Strengthening family involvement in elderly health management is key to improving nutritional outcomes for this vulnerable population.